MODELLING THE EFFECT OF INJECTION PRESSURE ON HEAT RELEASE PARAMETERS AND NITROGEN OXIDES IN DIRECT INJECTION DIESEL ENGINES - Yuksek, Levent; Sandalci, Tarkan; Ozener, Orkun; Ergenc, Alp Tekin (VINCA INST NUCLEAR SCI, 2014)
Investigation and modelling the effect of injection pressure on heat release parameters and engine-out nitrogen oxides are the main aim of this study. A zero-dimensional and multi-zone cylinder model was developed for estimation of the effect of injection pressure rise on performance parameters of diesel engine. Double-Wiebe rate of heat release global model was used to describe fuel combustion. Extended Zeldovich mechanism and partial equilibrium approach were used for modelling the formation of nitrogen oxides. Single cylinder, high pressure direct injection, electronically controlled, research engine bench was used for model calibration. 1000 and 1200 bar of fuel injection pressure were investigated while injection advance, injected fuel quantity and engine speed kept constant. The ignition delay of injected fuel reduced 0.4 crank angle with 1200 bar of injection pressure and similar effect observed in premixed combustion phase duration which reduced 0.2 crank angle. Rate of heat release of premixed combustion phase increased 1.75% with 1200 bar injection pressure. Multi-zone cylinder model showed good agreement with experimental in-cylinder pressure data. Also it was seen that the NO, formation model greatly predicted the engine-out NO emissions for both of the operation modes.
Keywords: Wiebe rate of heat release; multi-zone model; nitrogen oxide formation model; injection pressure; diesel engine combustion; Thermodynamics